Extraction and identification of the main compound present in Elaeis guineensis flower volatiles - Lajis, Md Nordin; Hussein, Mohd Yusof; Toia, Robert F. (Universiti Pertanian Malaysia, 1985)
The main compound contained in the volatile oils of the oil palm flowers was identified as l-methoxy-4 (2-propenyl) benzene or estragole. The same compound was extracted from the anthesizing male and female flowers of the oil palm (Elaeis guineensis). The newly identified compound is believed to be responsible for attracting the adults of the oil palm pollinating weevil, Elaeidobius kemerunicus (Coleoptera: Curculionidae). Steam distillation of1 kg of fresh male and female flowers yielded O.7g and O.2g of volatile oils. The chemical structure and characteristics were confirmed by mass spectromeric analysis, nuclear magnetic resonance (NMR) analysis, and the infrared spectra analysis. The possible usage of the compound in ecological research on the weevil and in the industry' are discussed.